Ethno-Sciences and the Transformation of Traditional Agricultural Systems in Teluk Bintuni: Between Preservation and Modernization - Jaizul, Alim; Sulistya, Astrid; Lianingsih, Nestia (Research Collaboration Community (RCC), 2025)
Traditional farming systems are a form of long-term interaction between humans and their environment that manifests ecological and cultural adaptation. This study aims to explore the dynamics between the preservation of local knowledge and the pressures of modernization in the transformation of traditional farming systems of indigenous peoples in Teluk Bintuni, West Papua. Using an ethno-science approach with qualitative-descriptive methods through participatory observation, in-depth interviews, FGDs, and documentation studies in the Moskona, Wamesa, and Sumuri indigenous communities. The results of the study indicate that traditional farming systems are still maintained with high dependence on sago (85%), sweet potatoes (72%), taro (66%), and bananas (54%) as sources of food and cultural identity. The transformation of the farming system does not follow a linear pattern from traditional to modern, but rather creates a hybrid system that selectively combines traditional elements with modern technology. Indigenous peoples are not passive in facing change, but actively negotiate and adapt based on their ecological and cultural interests. The ethno-science approach offers a framework for integrating local knowledge into development planning, without ignoring the ecological and spiritual dimensions of indigenous peoples. Dialogue between local knowledge systems and modern science can produce more adaptive and inclusive agricultural policies, especially in indigenous areas such as Teluk Bintuni that face pressure from natural resource exploitation.